Effect of different concentrations of propolis extract coating on postharvest quality of banana artificially inoculated with Colletotrichum gloesporioides - Ahmad Azfar Mohamad Areff,; Siti Nordahliawate Mohamed Sidique,; Mohd Nizam Lani,; Fauziah Tufail Ahmad, (Penerbit Universiti Kebangsaan Malaysia, 2022)
The coating is one of the methods to prevent postharvest loss in the food industry. Propolis seems to be promising as a coating due to its waxy properties, high antifungal activity and less toxicity. In this study, propolis ethanol extract coating was tested for the antifungal activity against Colletotrichum gloeosporioides, the causative fungus that caused anthracnose disease on bananas (Musa acuminata). All samples were artificially inoculated with C. gloeosporioides and the disease severity index (DSI) was measured. Other postharvest qualities of banana tested were weight loss, total soluble solids (TSS), colour and titratable acidity (TA). Results showed that the control banana was more susceptible to the fungal infection (60% necrosis) compared to the treated banana. The propolis coating successfully inhibited the fungus activity of C. gloeosporioides activity on a banana during storage. The higher concentration of extract coating seems to be better effective against the fungus. Moreover, the control banana showed higher weight loss (6.92%) and total soluble solid (p<0.05) compared to coated banana during storage. In conclusion, bananas treated with an 11% concentration of propolis coating are promising for improving the colour, total soluble solid content and titratable acidity and can inhibit artificially anthracnose disease caused by C. gloeosporioides on a banana.